Supporting the implementation of written exposure therapy for posttraumatic stress disorder in an obstetrics-substance use disorder clinic in the Northeastern United States - Sarah E. Valentine; Laura B. Godfrey; Resham Gellatly; Emilie Paul; Caitlin Clark; Karissa Giovannini; Kelley A. Saia; Yael I. Nillni (Elsevier, 2023)
Pregnant people with comorbid posttraumatic stress disorder (PTSD) and substance use disorder (SUD) constitute a highly vulnerable population. PTSD and SUD confer risks to both the pregnant person and the fetus, including a host of physical and mental health consequences. When PTSD and SUD co-occur, potential negative impacts are amplified, and the symptoms of each may exacerbate and maintain the other. Pregnancy often increases engagement in the healthcare system, presenting a unique and critical opportunity to provide PTSD and SUD treatment to birthing people motivated to mitigate risks of losing custody of their children. This paper presents implementation process outcomes of Written Exposure Therapy (WET), a brief, scalable, and sustainable evidence-based PTSD treatment delivered to pregnant persons receiving care in an integrated obstetrical-addiction recovery program at Boston Medical Center. Trial participants (N = 18) were mostly White, non-Hispanic (61.1%), not currently working (77.8%), had a high school or lower level of education (55.5%), had an annual household income less than $35,000 (94.4%), and were living in a substance use residential program (55.6%). We examined intervention feasibility, acceptability, appropriateness, adoption; barriers and facilitators to implementation; and feedback on supporting uptake and sustainability of the intervention using coded qualitative sources (consultation field notes [N = 47] and semi-structured interviews [N = 5]) from providers involved in trial planning and treatment delivery. Results reflected high acceptability, appropriateness, and adoption of WET. Participants described system-, provider-, and patient-level barriers to implementation, offered suggestions to enhance uptake, but did not raise concerns about core components of the intervention. Findings suggest that WET is an appropriate and acceptable PTSD treatment for this difficult-to-reach, complex population, and has the potential to positively impact pregnant persons and their children.